Videolaringoscopia versus laringoscopia direta para intubação traqueal em neonatos - Lingappan, Krithika; Neveln, Nicole; L Arnold, Jennifer; J Fernandes, Caraciolo; Pammi, Mohan (LAJEC - Latin American Journal of Emergency Care, 2024)
-